2023
DOI: 10.1021/acs.jpcb.3c00300
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependence of Dynamics and Structure among Hydrated Magnesium Ions: An Ultrafast Infrared Study

Abstract: The dynamics of aqueous magnesium chloride solutions, from relatively dilute (0.5 m) to near saturated (4.2 m) concentrations, were investigated using ultrafast two dimensional infrared and polarization selective pump-probe spectroscopies. The experiments were performed on two spectrally distinct nitrile stretch frequencies of the selenocyanate vibrational probe, corresponding to the CN nitrogen lone pair being associated with water and with Mg2+. No chemical exchange of the two species was observed over the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 87 publications
(203 reference statements)
2
16
0
Order By: Relevance
“…Figure shows the area-normalized, background-subtracted linear absorption spectra of SeCN – in confined aqueous MgCl 2 solutions of varying concentrations. As was previously observed in the bulk study of the same aqueous MgCl 2 solutions, there are two peaks centered at ∼2075 and ∼2115 cm –1 . The lower frequency peak (2075 cm –1 ) arises from the CN with its nitrogen lone pair hydrogen bonded to the OD of D 2 O (“D 2 O-associated peak”).…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Figure shows the area-normalized, background-subtracted linear absorption spectra of SeCN – in confined aqueous MgCl 2 solutions of varying concentrations. As was previously observed in the bulk study of the same aqueous MgCl 2 solutions, there are two peaks centered at ∼2075 and ∼2115 cm –1 . The lower frequency peak (2075 cm –1 ) arises from the CN with its nitrogen lone pair hydrogen bonded to the OD of D 2 O (“D 2 O-associated peak”).…”
Section: Resultssupporting
confidence: 60%
“…Linewidth increase can result from inhomogeneous or homogeneous broadening. In the bulk study, the observed line broadening with increasing concentration was attributed to inhomogeneous broadening, which arises from increased variety in solvent configurations . This was supported by the concentration independence of the homogeneous linewidths measured with 2D IR experiments.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations